On the Choice of Funtional Form for Hedonic Price Functions - Cropper, Maureen L.; Deck, Leland B.; McConnell, Kenenth E. (The Review of Economics and Statistics, 1988)
This study examines how errors in measuring marginal attribute pric es vary with the form of the hedonic price function. In simulations, consumers with known utility functions bid for houses with given attributes. Various forms of the hedonic function are estimated using equilibrium housing prices. Errors in estimating marginal attribute prices are calculated by comparing each consumer's equilibrium marginal bid vector with the gradient of the hedonic function. When all attributes are observed, linear and quadratic Box-Cox forms produce lowest mean percentage errors; however, when some attributes are unobserved or are replaced by proxies, linear and linear Box-Cox functions perform best. Copyright 1988 by MIT Press.